Heavy metal concentrations in edible muscle of whitecheek shark, Carcharhinus dussumieri (elasmobranchii, chondrichthyes) from the Persian Gulf: A food safety issue. (November 2016) - Adel, Milad; Oliveri Conti, Gea; Dadar, Maryam; Mahjoub, Masoud; Copat, Chiara; Ferrante, Margherita
Abstract: Together with several health benefits, fish meat could lead to heavy metal intoxication of consumers. In this study, we discuss Zn, Cu, Pb, Hg and Cd concentrations in fillets of forty specimens of Carcharhinus dussumieri, analyzed with atomic adsorption spectroscopy (AAS). The potential human health risks due to consumption of C. dussumieri was assessed by estimating average daily intake (EDI) and target hazard quotient (THQ) of metals. The average concentrations of metals measured in this study were (ppm dry weight): Cu 7.49 ± 0.25; Zn 3.47 ± 0.26; Pb 0.12 ± 0.03; Hg 0.028 ± 0.02; Cd 0.11 ± 0.03. Our results showed that no metal exceeded the EC and FAO limits. Cu and Cd accumulate in muscles with a body length (age)-dependent manner. The exposure daily intake of all toxic metals analyzed was found lower than the PTDI provided by WHO and the THQ resulted lower than 1, suggesting no risk for human health derived from consumption. Highlights: Trace elements in muscle of Carcharhinus dussumieri from Persian Gulf were been analyzed. Metals concentrations do not exceed the European limits for human consumption. Cd and Cu accumulate in muscles with a body length (age)-dependent manner. The EDI of all metals was lower than the PTDI provided by WHO and, THQ was <1.